Some observations on deformation banding and correlated microstructures of two aluminum alloys compressed at different temperatures and strain rates - Kulkarni, S.S; Starke, E.A; Kuhlmann-Wilsdorf, D (Acta materialia, 1998)
In compressed samples of high-purity aluminum alloys, without (Al–0.5 wt% Cu) and with hard precipitates (Al–0.5 wt% Cu–1.0 wt% Si), a variety of deformation band patterns has been observed, including occasional exquisite detailed structuring. According to the present preliminary results, the banding does not significantly depend on strain rates between 0.05 and 100%/s, nor on temperature from ambient to cryogenic (−193°C). However, it is greatly decreased by the presence of precipitates in the Al–Cu–Si alloy and was barely if at all visible at and above 200°C. The banding is due to changing selections of operating slip systems, falling short of the five required in the Taylor model of homologous deformation in polycrystals. The occasional exquisite detail in the banding pattern is accepted as virtual proof of the low-energy dislocation structure (LEDS) hypothesis, the basic tenet from which the LEDS theory of crystal plasticity follows without further assumptions. In agreement with this interpretation, also the underlying dislocation cell structure, which did not reveal any evident correlation with the deformation banding, as well as the observed workhardening features as dependent on strain rate and temperature are in accord with the LEDS theory.